Bunionette: Minimally Invasive and Percutaneous Techniques: A Topical Review of the Literature. Issue 2 (April 2017) - Ceccarini, Paolo; Rinonapoli, Giuseppe; Nardi, Andrea; Bisaccia, Michele; Di Giacomo, Lorenzo Maria; Caraffa, Auro
Purpose . The purpose of this study is to review the most recent literature available on the treatment of bunionette (also named tailor's bunion) with percutaneous and minimally invasive techniques. Focusing especially on clinical outcomes, studies related to this type of techniques were examined in order to evaluate the success of this practice that is, fusion rate and complications. The hypothesis is that these techniques are safe and successful procedures. Methods . In July 2015, a topical review of the PubMed/MEDLINE, EMBASE, and Google Scholar databases was conducted using the keywords percutaneous (OR mini-invasive OR minimally invasive) AND bunionette (OR tailor's bunion) AND treatment (OR surgery). Studies reporting the outcomes of the surgical treatment of bunionette were also included in our review. Results . The search yielded a total of 111 publications from PubMed/MEDLINE, EMBASE, and Google Scholar. After evaluating abstracts and full-text reviews, 9 articles were included in this review. Treatment methods were divided into 2 main surgical treatment categories: with or without fixation of the osteotomy. The most commonly used technique was that with fixation. The scores of success for techniques with and without fixation were 93.5 and 97.8, respectively. Conclusion . The current evidence for the treatment of bunionette deformity is limited to retrospective case series. Therefore, no conclusion can be made regarding the gold standard technique for bunionette deformity. The results published are very satisfactory, but the literature is still poor. Levels of Evidence: IV: Topical review